A Case of Emphysematous Osteomyelitis of the Midfoot: Imaging Findings and Review of the Literature. (9th June 2014) - Mautone, Marcela; Gray, Jessica; Naidoo, Parm
Abstract : Emphysematous osteomyelitis is a rare but potentially fatal condition that must be considered whenever intraosseous gas is identified on imaging. The organisms implicated in most cases of emphysematous osteomyelitis are anaerobes or members of the Enterobacteriaceae family. Significant comorbidities, such as malignancy and diabetes mellitus, frequently predispose to this condition, and high mortality rates have been reported. The radiologist must be aware of the implications of identifying intraosseous gas in order to facilitate early diagnosis and expedite management. We report a unique case of a 58-year-old male with diabetes mellitus who presented with emphysematous osteomyelitis of the midfoot and necrotising fasciitis of the ipsilateral distal lower limb. Specimen cultures in this case revealed a pure growth of Group G Streptococcus .